Desenvolvimento de liderança em uma instituição de qualificação profissional em saúde: um estudo de caso - Bello, Gabriela Brenner (Universidade do Vale do Rio dos Sinos, 2016)
The development of new leaders is a very common theme in organizations because companies have to deal frequently with changes and adversities to achieve significant performance and results. This article aims to analyze the development of the leadership competency in a professional health training institute. It also seeks to describe the managerial competences needed for the leader, indicate the abilities to be developed according to the perception of managers and leaders, and finally, analyze the factors that may encourage professionals in search of leadership development. The approach of this article is qualitative, and the research strategy is the case study. For data collection, observation and analysis of documents were conducted. It was also performed a focus group with supervisors and individual interviews with the counseling team of IPGS - Institute for Research, Education and Management in Healthcare. The results of this study indicate that the competence of leadership, when broadly approached and considering different aspects, can take the organization to the achievement of positive results. However, time and financial investment are required to the companies that intend to follow this path.
Keywords: Liderança; Gestão de pessoas; Desenvolvimento de competências; Leadership; People management; Competences development